Effectiveness of Routine and Booster Pertussis Vaccination in Children and Adolescents, Federal State of Brandenburg, Germany, 2002–2012. Issue 5 (May 2015) - Haller, Sebastian; Dehnert, Manuel; Karagiannis, Ioannis; Rieck, Thorsten; Siffczyk, Claudia; Wichmann, Ole; Poethko-Mueller, Christina; Hellenbrand, Wiebke
Abstract : Background: In Germany, whole-cell pertussis vaccines were rapidly replaced by high-concentration acellular pertussis-containing vaccines (3+1 doses from 2 months of age) starting in 1995. Boosters were recommended for 9- to 17-year-olds (2000) and for 5- to 6-year-olds (2006). Pertussis incidence remains high despite rising vaccination coverage (VC). Therefore, we analyzed VC and vaccine effectiveness (VE) in the federal state of Brandenburg. Methods: In a stratified case–cohort analysis, we compared VC of reported pertussis cases with VC assessed in schools and kindergartens in the following strata: Children aged 2–3 years born 2005–2009 (toddlers), 5–7 years born 1995–2006 (pre-schoolers) and 15–16 years born 1995–1996 (adolescents). We calculated VE for primary and booster vaccination using Poisson regression. Results: Four-dose VE decreased from 96.9% in toddlers [95% confidence interval (CI): 72.2–99.3] to 87.8% in pre-schoolers (95% CI: 79.7–92.7) to 81.7% in adolescents (95% CI: 40.6–92.8). Four-dose VE was lower in pre-schoolers born after 1996 (75.4%) than in those born 1995–1996, 1% and 21% of whom had received ≥1 dose of whole-cell pertussis vaccines, respectively. VE was higher in pre-schoolers and adolescents who received a booster (92.8%and 96.5%, respectively). However, overall booster VC was only 19% and 76% in these age groups, respectively. Conclusions: We observed high VE of routine pertussis vaccination, with evidence of waning over time and improved VE after booster vaccination. Increased uptake and monitoring of recommended pertussis boosters is urgently recommended to decrease high pertussis morbidity particularly in older children and adolescents.